Remote Laboratories: Approaches for the Future - Lindsay, Euan; Long, P.; Imbrie, P. (Stipes Publishing LLC, 2007)
Laboratory classes are an integral part of engineering education, but they are resource intensive impose significant logistical constraints upon the curriculum. One option to reduce these burdens is the use of remote laboratory classes – where students interact with the hardware at a distance, rather than in the traditional laboratory environment. Remote laboratories are an increasingly popular innovation in engineering education, but their development has for the large part been an ad hoc process - they are developed in isolation to address the needs of a particular laboratory class; and they are often regarded as a “second-best” substitute for the real thing. This workshop is aimed at fostering a more strategic approach to the future development of remote laboratory classes, from both pedagogical and logistical viewpoints. Throughout this workshop it our intent to access existing remote laboratories across multiple engineering disciplines to illustrate important characteristics.